Impact of radioiodine treatment on acute phase proteins in hyperthyroid cats. Issue 4 (April 2022) - Glück, Katharina; Mohrs, Sabrina; Hazuchova, Katarina; Bauer, Natali; Neiger, Reto
Objectives: The aim of this study was to investigate the impact of radioiodine treatment (RIT) on the acute phase proteins (APPs) serum amyloid A (SAA), alpha-1-acid glycoprotein (AGP) and haptoglobin (Hp) in hyperthyroid cats. Methods: Between June 2013 and November 2014, 33 hyperthyroid cats without clinical or laboratory signs of inflammatory or neoplastic disease and a body weight >2.5 kg were enrolled. Immediately before, and 12, 36, 72 h and 6 days after RIT, serum samples were obtained for determination of APP concentrations. Results: Both SAA and AGP concentrations changed significantly after RIT. The concentration of AGP increased gradually after treatment with a maximum concentration at the end of the study period (median baseline 398 μg/ml; median 6 days post-RIT 562 μg/ml [ P = 0.001]). A relevant >two-fold increase in AGP was seen in 8/33 (24%) cats. SAA concentration increased significantly within 12 h (baseline 9.2 μg/ml; 12 h post-RIT 22.5 μg/ml [ P = 0.012]). In 7/33 (21%) cats, a clinically relevant >10-fold increase in SAA was observed. Hp concentration showed no significant change ( P = 0.12). Conclusions and relevance: RIT induced a mild, mainly not clinically relevant acute phase reaction (APR). AGP and SAA were useful APPs to determine RIT-induced APR.